The Effect of Differentiated Learning on Students' Learning Outcomes of Pancasila Education - Susi Susi; Siti Mariyatul Koimah; Roni Rustandi; Nurdiyana Nurdiyana (Jurnal Pemberdayaan Masyarakat, 2025)
This research investigates the influence of differentiated learning models on student achievement in Pancasila Education at MTS Asmaul Husna, Tangerang Regency. Differentiated learning is a learning approach that adjusts content, process, and product to meet differences in student readiness, interest, and learning style. The study used a quantitative design with a quasi-experimental method, specifically the pretest–post-test nonequivalent control group design. The participants were class VII A (26 students) as the experimental group and class VII B (22 students) as the control group, determined through saturated sampling. Data were gathered using multiple-choice tests and analyzed for normality, homogeneity, and independent-samples t-tests. The findings revealed that the experimental group's mean post-test score was 82.58, compared with 74.18 in the control group. The significance value (Sig. 2-tailed) of 0.006 0.05 indicates a significant difference. These results demonstrate that differentiated learning has a positive effect on learning outcomes. This study enriches educational knowledge by presenting empirical evidence of the effectiveness of differentiated learning in improving student performance and can serve as a reference for future pedagogical innovation. This research contributes theoretically by enriching knowledge and practically by guiding effective differentiated learning.